PERAN GAYA KEPEMIMPINAN DAN IKLIM ORGANISASI TERHADAP KINERJA GURU SMP NEGERI DI KECAMATAN TAYU DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING - 1152020122, Giyarto (Jurnal Mahasiswa Pasca Sarjana, 2013)
The aim of this study is to examine the role of leadership style and organizational climate on the teachers performance of junior high school in the District of Tayu with organizational commitment as an intervining variable. The usefulness of this study to clarify and extend previous research on the role of leadership style and organizational climate on the performance of junior high school teachers in the District of Tayu with organizational commitment as a interviningvariable. This research uses a quantitative approach is supported by qualitative descriptive analysis. The population was teachers of junior high school in the district of Tayu, amount to 112 people. The research usescensus techniques, which all as the sample of population. Techniques of data analysis starts from instrument test, the classical assumption test, models test, goodness of fit test, regression analysis, hypothesis test and mediation test. The study of teachers of junior high school in the district of Tayu showed: (1) leadership style did not significantly influence organizational commitment, (2) organizational climate significantly influenced organizational commitment, (3) leadership style significantly influenced on the teacher performance, (4) organizational climate significantly influenced on the teacher performance, (5) organizational commitment significantly influenced the teacherâs performance, (6) in effective organizational commitment to mediate the effect of leadership style on teachers performance, and (7) ineffective organizational commitment to mediate the effect of organizational climate on teachers performance. Keywords: leadership styles, organizational climate, teacher performance, and organizational commitment